KEPEMIMPINAN DALAM PENINGKATAN KINERJA GURU DI TK ISLAM AR-RIFQI - Ayuni; Hafiani Aulia; Resika Cahyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The principal’s leadership plays a strategic role in determining the success of educational institutions. This study aims to describe the influence of school leadership on improving teacher performance through motivation, supervision, and professional development. This research uses a descriptive qualitative approach with data collected through interviews, observation, and documentation. The results show that transformational and participative leadership styles have a positive impact on teacher performance, particularly in terms of responsibility, discipline, and innovation in the teaching process. Communicative and inspiring leadership is proven to create a conducive work environment and enhance teachers’ motivation and professionalism.